Legal audit : a tool for assessing the quality of financial information - Literature review - AIT LEMQEDDEM , Hamid; BOULAHSEN , Mohamed Khalil (Revue du contrôle, de la comptabilité et de l’audit, 2022)
This literature review aims to present a reading of previous research that has treated our topic on legal audit consideration as a tool that can assess the quality of financial information, that is considered as a heated debate in the recent years within organizations in order to make it more credible for all stakeholders and be able to reduce the problem of asymmetric financial reporting between these parties. The intervention of the legal auditor emphasizes a continuous debate on its importance and the obligation to improve the quality of financial information and financial security as a means to increase the substance of financial reporting. More specifically, we will present the impact of the quality of the legal auditor on the reliability of financial communications by mobilizing some theories that have put the relationship between the quality of financial information and other variables on the quality of financial reporting legal audit firm.